Evaluation of physical, chemical and microbiological parameters of informal raw milk packaged in bottles - PET marketed in peripheral neighborhoods in a municipality in the northern region of Brazil (Research, Society and Development, 2022)
Milk is one of nature's most complete foods due to its nutritional constituents, making it susceptible to contamination by pathogenic microorganisms. The study aimed to evaluate the physical-chemical parameters acidity, density, lipids, proteins, pH and microbiological through the standard counting in plates of informal raw milk bottled in PET bottles sold and consumed in four different neighborhoods of a municipality located in the northern region of Brazil. The samples were stored in a thermal box containing ice and transported to the Microbiology and Food Analysis Laboratories of the Instituto Federal do Tocantins – IFTO, Paraíso do Tocantins campus, for physical-chemical and microbiological analyses. The samples were coded in: A, B, C and D. The experimental design was completely randomized (DIC) with four (4) treatments and ten (10) replications. In order to verify occurrences of differences between the means of the response variables, ANOVA analysis of variance and Tukey's test were applied at a 5% significance level. Principal Component Analysis (PCA), a multivariate analysis technique, was used and analyzed the data in which treatments are related by interrelated response variables, grouping similar physicochemical variables. The physical-chemical evaluation of milk acidity showed average values ​​(0.19g lactic acid/100 mL) in disagreement with the values ​​recommended in MAPA IN nº76/2018. The microbiological analysis showed values ​​(3.3x105 to 3.5x105 CFU/mL) above those established by legislation, indicating that the milk was obtained and marketed under improper hygienic-sanitary conditions. It is suggested greater attention from inspection bodies, in order to prevent the purchase by consumers and possible food contamination, in addition to campaigns to clarify the risks and possible health problems arising from the consumption of informal unpasteurized milk.